Answer:
You need to add 1/36th to both sides of the equation, giving you the expression
[tex]n^2 - \frac{1}{3}n + \frac{1}{36} = 7\frac{1}{36}\\[/tex]
Which can be expressed as:
[tex](n - \frac{1}{6})^2 = 7\frac{1}{36}[/tex]
Step-by-step explanation:
We need to add a term that is the the square of half the coefficient of the second term.
[tex]n^2 - n/3 = 7\\n^2 - \frac{1}{3}n = 7\\n^2 - \frac{1}{3}n + \frac{1}{36} = 7\frac{1}{36}\\(n - \frac{1}{6})^2 = 7\frac{1}{36}[/tex]
Let's check the answer by expanding:
[tex](n - \frac{1}{6})^2 = 7\frac{1}{36}\\n^2 - \frac{1}{6}n - \frac{1}{6}n + \frac{1}{36} = 7\frac{1}{36}\\n^2 - \frac{1}{3}n + \frac{1}{36} = 7\frac{1}{36}\\n^2 - \frac{1}{3}n = 7[/tex]
Which verifies the answer.